2018
DOI: 10.1080/14760584.2018.1506333
|View full text |Cite
|
Sign up to set email alerts
|

Polio endgame risks and the possibility of restarting the use of oral poliovirus vaccine

Abstract: Introduction: Ending all cases of poliomyelitis requires successful cessation of all oral poliovirus vaccine (OPV), but the Global Polio Eradication Initiative (GPEI) partners should consider the possibility of an OPV restart.Areas covered: We review the risks of continued live poliovirus transmission after OPV cessation and characterize events that led to OPV restart in a global model that focused on identifying optimal strategies for OPV cessation and the polio endgame. Numerous different types of events tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 54 publications
(109 reference statements)
0
53
0
Order By: Relevance
“…Subsequent modelling studies indicated that polio eradication, as compared with control, would be more cost-effective and ultimately incur substantial net benefits 8 9. These studies were, however, criticised as depending on untenable or at least highly optimistic assumptions 10–12…”
Section: Early But Truncated Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent modelling studies indicated that polio eradication, as compared with control, would be more cost-effective and ultimately incur substantial net benefits 8 9. These studies were, however, criticised as depending on untenable or at least highly optimistic assumptions 10–12…”
Section: Early But Truncated Successmentioning
confidence: 99%
“…The current DRC epidemic has emerged in different provinces as independent cVDPV type 2 outbreaks, which now threatens to spread to other neighbouring countries and may endanger the whole of sub-Saharan Africa (SSA) 3 5. By 2016, 155 countries had already replaced trivalent OPV with a bivalent (types 1 and 3) vaccine; the DRC outbreak thus demonstrates the weaknesses in polio surveillance systems and—if not contained—may cause a general move back to the trivalent OPV 3 4 10 24…”
Section: Challenging Epidemiolgical Developmentsmentioning
confidence: 99%
“…cVDPVs have been designated a Public Health Emergency of International Concern, for which the only effective control is use of stockpiled monovalent OPV2. Use of this vaccine carries the inherent risk of seeding new cVDPVs, particularly with waning mucosal immunity of the population following OPV2 cessation 8, 9. IPV use cannot generate cVDPVs but these vaccines do not induce primary intestinal mucosal immunity, so IPV use is ineffective in interrupting transmission in settings where transmission is predominantly via the faecal–oral route 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…In our model, the total (‘all serotypes’) would continue to increase until the last OPV cessation. In addition to these possibilities, OPV2 cessation did not go as smoothly as hoped, and the use of monovalent OPV2 continues to date (as of August 2019) in response to cVDPV2 outbreaks[54]. This means that the model should include the possibility of creating some new iVDPV2 excreters in the areas of serotype 2 outbreaks.…”
Section: Discussionmentioning
confidence: 99%